2022
DOI: 10.4103/jfmpc.jfmpc_1095_21
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 infection among health care workers in a tertiary care teaching hospital in Kerala – India

Abstract: Health care workers are at the frontline for management and containment of COVID-19 infection which has put them at additional risk of the disease. Infection and subsequent quarantine of contacts among HCW may produce considerable strain on the health care system. It is essential that we study the modes by which HCW may get infected in the work environment. Methods: All HCW testing positive for SARS COV 2 from 1 st March 2020 to 31 st … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…This finding aligns with that of another study conducted at a COVID-19-care hospital in Mumbai, where 85% of the HCWs with COVID-19 infection were symptomatic [9]. However, Chandran et al (2022), in their study conducted in Kerela, in southern India, reported a lower proportion (67%) of symptomatic cases among SARS-CoV-2-positive HCWs [10]. In a study conducted in Italy, Magnavita et al…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This finding aligns with that of another study conducted at a COVID-19-care hospital in Mumbai, where 85% of the HCWs with COVID-19 infection were symptomatic [9]. However, Chandran et al (2022), in their study conducted in Kerela, in southern India, reported a lower proportion (67%) of symptomatic cases among SARS-CoV-2-positive HCWs [10]. In a study conducted in Italy, Magnavita et al…”
Section: Discussionsupporting
confidence: 78%
“…This may be due to the difference in adherence to IPC measures, training status, and exposure to patients and their surroundings. In a previous study conducted at the current study site, it was reported that informal workplace interactions (having meals together) and inconsistent use of masks during routine work (39.6%) were the most common causes of high-risk exposure among HCWs, as compared to the patient care activities without appropriate PPE (20.4%) [10]. In a prospective study involving 1,344 HCWs in Paris, Contejean et al (2020) also reported that major reasons for SARS-CoV-2 infection were contact without PPE with an index case, and taking off masks during breaks in the presence of colleagues [15].…”
Section: Discussionmentioning
confidence: 79%
“…In our study, we calibrated the transmission, recovery and death rates parameters for modelling COVID-19 among the healthcare professionals. The model obtained the estimated incidence of COVID-19 of 3–8%, falling within the range of incidence reported among the healthcare staff in India setting [ 37 ]. Another strength of the study is that on considering the lower willingness-to-pay threshold for India ($115-$770), even at the lower estimated threshold of India’s GDP per capita, the conclusions of the results remained unchanged.…”
Section: Discussionmentioning
confidence: 62%
“…The practice of universal masking at all times is challenging, and inevitable breakdowns have occurred during mealtimes and in shared accommodations. [ 7 ] Although they knew their risk of becoming infected, some healthcare providers prepared themselves and their families to combat the situation. However, they were worried and helpless when they got a COVID-19–positive report.…”
Section: Discussionmentioning
confidence: 99%